Triterpenic acids from Eugenia moraviana - Lunardi Inês (Journal of the Brazilian Chemical Society, 2001)
A novel triterpene, characterized as 6alpha-hydroxybetulinic acid, was isolated from the leaves and stems of Eugenia moraviana (Myrtaceae), known in Brazil as Cambuí, together with three known compounds, platanic acid, betulinic acid and beta-sitosterol. Unequivocal ¹H and 13C assignments of 6alpha-hydroxybetulinic acid (3beta,6alpha-dihydroxy-20(29)-lupen-28-oic acid) and platanic acid were undertaken by spectral analysis including NOE and 2 D NMR experiments.